2011
DOI: 10.4314/ijest.v2i8.63841
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of &#947- and α-Fe<sub>2</sub>O<sub>3</sub> nano powders synthesized by emulsion precipitation-calcination route and rheological behaviour of α-Fe<sub>2</sub>O<sub>3</sub>

Abstract: Nano crystals of γ-Fe 2 O 3 (maghemite) were synthesized by emulsion precipitation method using kerosene as oil phase, SPAN-80 (sorbitane monooleate) as the surfactant and sodium hydroxide as the precipitating agent. The characterization of the samples by FTIR (Fourier transform infra-red) and XRD (X-ray diffraction) techniques confirmed the formation of γ-Fe 2 O 3 (maghemite). Analysis by SEM (scanning electron microscope) and TEM (transmission electron microscope) was carried out to study the morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 40 publications
7
43
0
2
Order By: Relevance
“…Nano sized α-Fe 2 O 3 (70nm) was prepared through emulsion route as described in literature [35]. Nano Al (100nm) was obtained from SIBTERMOCHIM Ltd, Russia.…”
Section: Methodsmentioning
confidence: 99%
“…Nano sized α-Fe 2 O 3 (70nm) was prepared through emulsion route as described in literature [35]. Nano Al (100nm) was obtained from SIBTERMOCHIM Ltd, Russia.…”
Section: Methodsmentioning
confidence: 99%
“…However, the intensity of the vibration IR spectra decreased as the amount of Fe increased. Several studies have reported observations where the IR spectrum of ferric oxide (Fe 2 O 3 ) between 560-460 cm −1 may have overlapped with the Ti-O-Ti vibration peak at 766 cm −1 , causing this peak to diminish as the amount of Fe increased [21,22]. The vibration peak recorded at 1390 cm −1 represented the C=O stretching related to carboxylic groups and carboxylate moieties [23,24], while the presence of C=O stretching could be due to the oxidation treatment of AC with nitric acid.…”
Section: Photodegradation Studymentioning
confidence: 99%
“…Sintesis nanopartikel magnetik besi sudah banyak dilakukan antara lain dengan menggunakan metode irradiasi electron beam, metode kopresipitasi, metode presipitasi emulsi (Zhao et al, 2007;Layek et al, 2010;Sahoo et al, 2010). Oleh karena nanopartikel besi bersifat toksis terhadap tubuh manusia, dalam bioaplikasi, nanopartikel ini harus dilapisi terlebih dahulu dengan material lain.…”
Section: Pendahuluanunclassified